Association of Time Between Radiation and Salvage APR and Margin Status in Patients With Anal Cancer Treated With Concurrent Chemoradiation. Issue 6 (June 2020) - Lee, Grace C.; Ricciardi, Rocco; Stafford, Caitlin; Hong, Theodore S.; Francone, Todd D.; Bordeianou, Liliana G.; Kunitake, Hiroko
There is a controversy regarding the optimal time to assess anal squamous cell carcinoma (SCC) response to chemoradiation and when salvage abdominoperineal resection (APR) should be offered. A retrospective cohort study was performed on patients with stage I–III anal SCC treated with chemoradiation in the National Cancer Database (2004–2015). The time between radiation and APR was recorded. Logistic regression and Cox proportional hazard analysis were used to determine predictors of resection margin status and overall survival. The cohort included 23 050 patients, of whom 545 (2.4%) underwent salvage APR. The median (IQR) time between radiation and resection was 3.8 (2.4-5.5) months. The rate of positive margins was 19.0%. Positive margins were more common in male, non-white patients with larger tumors, pathologic upstaging of T stage, and ≥3 months between chemoradiation and resection (all P < .05). Observing for ≥3 months between chemoradiation and APR remained associated with positive margins, even after adjusting for pretreatment tumor size (odds ratio = 2.56, 95% CI 1.46-4.47). Our data, based on the largest published cohort of anal SCC patients treated with chemoradiation and subsequent APR, suggest that patients at high risk of local treatment failure, particularly non-white men with large tumors, may benefit from early interim restaging and earlier consideration of salvage surgery.